Kotak Harta Karun: Media Pembelajaran Numerasi Berbasis AI dan Pola Berpikir Komputasi Anak Usia Dini - Kamiliyah, Zahirotul; Faruk, Roizatul; Charizah, Minnatin (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2025)
Early childhood education strives to prepare a generation that is not only academically intelligent, but also has strong computational thinking and numeracy skills. This study aims to explore the use of artificial intelligence-based numeracy learning media in developing computational thinking patterns in early childhood. The method used is qualitative descriptive, with literature studies to understand the phenomenon and design relevant learning applications. The steps in media development include needs, design analysis, interactive content creation, implementation, and revision based on feedback. The designed learning media, such as "Treasure Box", integrates gamification elements and AI technology to create a fun and effective learning experience. The results of the study show that this media can improve students' numeracy skills and stimulate creativity and problem-solving skills. This research is expected to make a significant contribution to improving the quality of PAUD education in the digital era.